Development of a food composition database of different food contaminants CONT11 and estimation of dietary exposure in children of southern Spain - Hinojosa-Nogueira, Daniel; Muros, José J.; Navajas Porras, Beatriz; Delgado-Osorio, Adriana; Pérez-Burillo, Sergio; Pastoriza, Silvia; Rufián-Henares, José Ángel (Elsevier, 2023)
Increasing food security is one of the Sustainable Development Goals. One of the main risks in food is the increase in food contaminants. Processing methods, such as the addition of additives or heat treatment, influence contaminant generation and increase their levels in food. The aim of the present study was to create a database using a methodology similar to that of food composition databases but with a focus on potential food contaminants. CONT11 collects information on 11 contaminants: hydroxymethyl-2-furfural, pyrraline, Amadori compounds, furosine, acrylamide, furan, polycyclic aromatic hydrocarbons, benzopyrene, nitrates, nitrites and nitrosamines. This is collected for more than 220 foods obtained from 35 different data sources. A food frequency questionnaire validated for use with children was used to validate the database. Contaminant intake and exposure in 114 children aged 10–11 years were estimated. Outcomes were within the range of values described by other studies, confirming the usefulness of CONT11. This database will allow nutrition researchers to go a step further in assessing dietary exposure to some food components and the association of this with disease, whilst also informing strategies to reduce exposure.
Keywords: Industria alimentaria - Control de calidad; Nutrición - Innovaciones tecnológicas; Food contaminants; Dietary exposure; Food composition database; Children